(untitled) (Research, Society and Development, 2018)
Although not addressed at all, the school local can also be a favorable place for the development of occupational diseases in the professionals who work there, especially in relation to the cognitive ergonomic aspect. Among the main agents that generate the risk is the incidence of noise. The presence of noise in classrooms can cause a number of damages to teachers’ health and, when above the normatively established limits, can cause behavioral and psychological disorders. In this sense, the objective of this study is to investigate, through quantitative and qualitative analysis, the damage capacity generated by the noise from the ergonomic point of view. The methods used in the research include a interview with teachers from a specific public institution located in the João Monlevade city. In addition, a quantitative evaluation of the continuous and intermittent noise level was also carried out through the use of a noise dosimeter. The analyzes were based on the assumption of acoustic comfort conditions, and aspects related to insalubrities were not considered. The results obtained were compared to the levels established for acoustic comfort by the Brazilian standards and related to the information obtained through the questionnaire. The results obtained demonstrate the need to adapt the activities of these professionals to the institution studied.